(untitled) (Research, Society and Development, 2020)
The importance of native forest seeds, free of phytopathogens, is a strategy for the implantation of quality forest plantations. The scarcity of information about the health conditions of seeds of native forest species causes the spread of diseases. The objective of this work was to determine a method of sanitary analysis to identify pathogens in seeds of the species of Austronium graveolens, Bauhinia forficata and Cordia trichotoma (Vell.). The treatments consisted of filter paper methods with and without disinfestation in the periods of seven and 15 days, 15 days with water restriction, with BDA medium by seven and 15 days and BDA medium with water restriction during 15 days. For each test, it was used 400 seeds. The results showed that for each forest specie seeds the best detection method was in a Petri dish with culture medium and seed disinfestation, the Austronium graveolens and Bauhinia forficata seeds need an incubation period of 15 days with water restriction and Cordia trichotoma (Vell.) seeds of seven days.